Development of Problem-Based Learning Student Worksheets to Train Critical Thinking Skills of Students in Biology Education Study Program - Widia Wulandari; Siti Darwa Suryani; Irwandi Irwandi (International Journal of Educational Research, 2025)
Critical thinking ability is one of the important competencies that students must possess in biology learning. This research aims to develop Problem-Based Learning (PBL) Student Worksheets to train students' critical thinking skills in Plant Anatomy courses. This research uses the Research and Development method with a simplified 4-D model consisting of three stages: Define, Design, and Develop. The research subjects were second-semester Biology Education Study Program students at Universitas Muhammadiyah Bengkulu. Research instruments included media and material expert validation sheets, as well as student response questionnaires. Validation was conducted by one media expert and one material expert, then tested on 5 students (limited trial) and 22 students (extensive trial). Validation results showed that the student worksheets received a "very valid" category with 86% from media experts and 88% from material experts. Practicality tests showed "very practical" results with 89% in limited trials and 91% in extensive trials. The developed student worksheets contained contextual problem scenarios, systematic PBL stages, and critical discussion questions that encourage students to analyze, evaluate, and conclude based on empirical data. This research concludes that PBL-based student worksheets are feasible to use as learning media to train students' critical thinking skills in Plant Anatomy courses.